Comparison of the Usefulness of SPE Cartridges for the Determination of β-Blockers and β-Agonists (Basic Drugs) in Environmental Aqueous Samples - Magda Caban; Piotr Stepnowski; Marek Kwiatkowski; Joanna Maszkowska; Marta Wagil; Jolanta Kumirska (Journal of Chemistry)
Even though the methodology used for the determination of β-blockers and β-agonists in environmental samples is based mainly on solid-phase extraction (SPE) and gas chromatography or liquid chromatography with mass spectrometric detection, the available literature data on the applied SPE procedures is rather sparse. In this paper such comparison is presented. Moreover, the usefulness of the eight SPE cartridges for the determination of five β-blockers (acebutolol, atenolol, metoprolol, nadolol, and propranolol) and two β-agonists (salbutamol and terbutaline) in environmental aqueous samples using GC techniques is tested. Among them, three (the trifunction sorbent Strata Screen C, the copolymers LiChrolut EN, and the functionalized copolymer Isolute ENV+) were used for the first time for this purpose. It was confirmed that polystyrene-divinylbenzene-N-vinylpyrrolidone copolymers (PS-DVB-VP, Strata-X, and Oasis HLB cartridges) have a better potential than a cation-exchange sorbent for the extraction of the target drugs from environmental water samples. However, it should be stressed out that the direct application of the tested SPE conditions for the analysis of real environmental water samples is not possible, and such parameters, like volume of loading sample, appropriate solvents for washing and elution steps, and so forth, must be optimized again in order to achieve satisfactory recovery values for the target compounds.